Updates on Hirsutism: A Narrative Review - Ramadan S. Hussein; Walid Kamal Abdelbasset (International Journal of Biomedicine, 2022)
Hirsutism is described as an abnormal amount of hair development in females in a male-like way. Excessive hair growth is frequently associated with severe emotional discomfort. Hirsutism is a frequent presentation to dermatologists, as women seek both aesthetic and therapeutic treatment options for their condition. Hirsutism is caused by an excess of androgens, most frequently from the ovary or adrenal glands. Hirsutism is frequently linked with metabolic disorders such as polycystic ovary syndrome (PCOS); it can also occur idiopathically, as a side effect of medicine, or, rarely, due to a serious underlying condition. This article discusses the diagnosis and treatment of hirsutism concisely.